An interdisciplinary approach aiding the diagnosis of primary progressive aphasia: A case report - Shigaeff,Nadia (2017)
ABSTRACT Frontotemporal dementia (FTD) is one of the most common causes of early-onset dementia with primary progressive aphasia (PPA) being the second-most-frequent form of this degenerative disease. Despite the similarity with progressive dementia (especially in early stages of Alzheimer´s disease), three types of PPA can be differentiated: semantic, agrammatic and logopenic (subtype discussed in this study). To date, no medications have been shown to improve or stabilize cognitive deficits in patients with PPA. We report the case of a 62-year-old woman with difficulty naming objects and planning. An interdisciplinary evaluation, including imaging and lab exams, together with neuropsychological and personality assessments, confirmed that the patient had logopenic PPA on the basis of repetition difficulty, phonemic and semantic paraphasias and absence of agrammatism. The timing of the assessment in this case, along with the resources available and commitment of an integrated interdisciplinary team, allowed a differential diagnosis (from other classical dementias) to be reached.